2013
DOI: 10.12816/0000265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Ecdysteroid Analog ( RH-0345 ) on the Ovarian and Testicular Components of Eupolybothrus Nudicornis ( Myriapoda : Chilopoda )

Abstract: We studied the effects of one ecdysteroid analog (RH-0345) on the ovarian and testicular components of the centipede Eupolybothrus nudicornis used as a model of predators of soil fauna. The injection of 10 µg of RH-0345 significantly reduced protein, lipid and carbohydrate concentrations in both the ovarian tissue of females and testicular tissue of males collected in spring or autumn. In consequence, this study shows that ecdysteroid analog pesticides can affect the reproduction of other arthropods than insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Proteins act as essential components of organisms' structural material, in contrast to that of carbohydrates and fats which are elements for energy supply. Moreover, protein plays an important role in all biological functions as they catalyze biochemical reactions, regulate hormones and share in cell structure (Daas-Maamcha et al 2013). The present results showed that plant oil treatments of the M. scalaris larvae resulted in a significant (p<0.05) increase in the total protein content in the whole body of third instar larvae treated as first instars with clove, orange and spearmint oils.…”
Section: Total Protein Contentmentioning
confidence: 48%
“…Proteins act as essential components of organisms' structural material, in contrast to that of carbohydrates and fats which are elements for energy supply. Moreover, protein plays an important role in all biological functions as they catalyze biochemical reactions, regulate hormones and share in cell structure (Daas-Maamcha et al 2013). The present results showed that plant oil treatments of the M. scalaris larvae resulted in a significant (p<0.05) increase in the total protein content in the whole body of third instar larvae treated as first instars with clove, orange and spearmint oils.…”
Section: Total Protein Contentmentioning
confidence: 48%